Studies on the effect of mercury on germination and biochemical changes of ground nut [Arachis hypogaea (L). var. VRI- 1] seedlings - G. Prabakaran, R. Pugalvendhan, P.S. Sharavanan (Recent Research in Science and Technology, 2009)
The uptake and accumulation of mercury in various parts of the plants namely stem, root, leaf and seeds showed a gradual decrease with the steady increase in mercury treatment. It can be concluded that the VRI-1 variety of groundnut was proved to be tolerant to mercury. Hence it can it is recommended that the variety VRI Ã¢â‚¬â€œ 1 can be cultivated in the soils contaminated with mercury and chloralkaliÃ‚Â plants which use mercury as an electrode in cells for the manufacture of caustic soda and chlorine effluent. This will prevent considerably the extent of damage caused by mercuryon ground nut to a certain extent.